Thiacloprid exposure disrupts the gut-liver axis and induces liver dysfunction in the Reeves' turtles (Mauremys reevesii) - Shuqin Lin; Yunjuan Xiao; Siyu Li; Liyan Tang; Haitao Shi; Meiling Hong; Li Ding (Ecotoxicology and Environmental Safety)
As one of the neonicotinoid insecticides, thiacloprid (THI) is extensively used in agriculture and frequently detected in various aquatic environments, posing a potential threat to aquatic organisms. However, the effects of THI exposure on aquatic turtles remain unknown. In this study, we focused on investigating whether THI has a toxic effect on the gut-liver axis in aquatic turtles. The Reeves' turtles (Mauremys reevesii) were exposed to 0.0178 μM, 6 μM, and 60 μM THI for 5 consecutive weeks. The results revealed that THI altered the composition of intestinal flora, with a decrease in the relative abundance of Romboutsia, and an increase in Clostridium_sensu_stricto_1, Cetobacterium, Enterococcus. This disruption of the intestinal barrier led to an increase in lipopolysaccharide (LPS), THI, and other harmful substances entering the liver. Metabolomic and transcriptomic analyses indicated that metabolic dysregulation and differences in gene expression were concentrated in amino acid metabolism and lipid metabolism, ultimately resulting in severe liver damage and steatosis. Furthermore, elevated levels of liver function indicators, including aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), total bile acid (TBA), and triglyceride (TG), were positively correlated with increased THI concentrations. Our findings demonstrate that THI impairs the intestinal barrier and causes liver dysfunction and damage in turtles, providing new insights into evaluating the toxic effects of thiacloprid on aquatic organisms.